2020
DOI: 10.1002/pssb.202000140
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Minor Addition of Oxygen on Bulk Metallic Glass Formation of Binary Cu–Zr Alloys via Containerless Processing

Abstract: The effect of oxygen content on the glass‐forming ability of binary Cu–Zr alloys is investigated by the in situ observation of the cooling process during the containerless solidification using an aerodynamic levitation technique. The oxygen content of ≈0.72 at% induces the crystallization of undercooled liquid Cu47Zr53 alloy, whereas that of ≈0.33 at% enhances the glass‐forming ability and leads to the formation of bulk metallic glass when compared with the alloy containing ≈0.20 at% of oxygen. The differentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Employing molecular dynamic simulation, it was discovered that minor addition of Y increased the icosahedra and Kasper polyhedra with high local five-fold symmetry in a MgCuY amorphous system and improved the GFA properties [27]. Mizuno et al [28] revealed that the minor addition of oxygen, even in ppm, led to the significant changes in the critical cooling rate of the glassy alloys.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Employing molecular dynamic simulation, it was discovered that minor addition of Y increased the icosahedra and Kasper polyhedra with high local five-fold symmetry in a MgCuY amorphous system and improved the GFA properties [27]. Mizuno et al [28] revealed that the minor addition of oxygen, even in ppm, led to the significant changes in the critical cooling rate of the glassy alloys.…”
Section: Introductionmentioning
confidence: 99%
“…According to literature [22,23,28], microalloying from metalloid elements to rare-earth ones may lead to the improvement of GFA and mechanical behaviors in the BMGs. However, the mechanisms for betterment of properties are still under debate.…”
Section: Introductionmentioning
confidence: 99%
“…[125] Only recently, Mizuno et al showed by synchrotron X-ray diffraction, that a small amount of oxygen in binary Cu-Zr could improve the glass-forming ability, which was explainable by an increased viscosity due to oxygen. [126] Containerless benchmark measurements of the viscosity of Cu 50 Zr 50 in the ISS-EML showed good agreement with MD simulations. [97] Further simulations show that the temperature-dependent viscosity of Cu 50 Zr 50 is related to the atomic packing evolution in the melt.…”
Section: Recent Resultsmentioning
confidence: 59%
“…According to Stokes–Einstein equation [32], the oxygen diffusion coefficient is inversely proportional to the dynamic viscosity of the solution. Previous experimental research showed the viscosity of some metallic glasses increases with higher oxygen concentrations [33,34]. Consequently, CP materials are presumably more viscous than HP ones.…”
Section: Resultsmentioning
confidence: 99%